Exploring farmers' perceptions of pawnshop’s role in farm financing using pawn services - Abdul Aziz Baihaqi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: In Indonesia, smallholder farmers in rural areas in South-East Lombok still rely heavily on agriculture. Its leading commodities include rice, corn, and tobacco, which are crucial for livelihoods and food security. The existence of smallholder farmers is essential to the growth of the local economy and food supply. However, they frequently encounter some obstacles when trying to raise official financing. One well-known state-owned pawnshop in Indonesia that offers funding alternatives for farmers to access capital is pawnshops. Methods: In this study, a qualitative descriptive method was employed, guided by SERVQUAL and SLF frameworks. Data collection was conducted through in-depth interviews with farmers who already use pawn services to fund their farming activities in South Lombok. Thematic analysis was used to analyse the data gathered. Findings: The study found that Farmers perceived pawn services by pawnshops positively, especially for its ease, speed, and convenience. Major customers value its people. However, problems remain faced by customers when accessing the service, especially for non-gold assets, and there is no adequate information about the funding scheme for farmers. Despite the findings supporting major dimensions of the SERVQUAL framework, the challenges revealed gaps for the SLF, which promotes inclusion to sustainable livelihood in agricultural activities. Conclusion: Farmers in South Lombok rely on pawnshops for funding because they have limited access to official loans. They appreciate its quick and easy gold-pawning services, while severe restrictions for non-gold items and a lack of farmer-specific programs limit accessibility. This study emphasises the importance of simpler procedures, digital verification, flexible repayment schedules coordinated with harvest cycles, and improved information outreach. Novelty/Originality of this article: This study provides valuable insights on the role of pawn-based services in an underexplored segment and region like South Lombok, especially in the agricultural context.